Implementasi Supervisi Akademik dalam Meningkatkan Kompetensi Pedagogik Guru di SMA Negeri 1 Gubug - Pratiwi, Ari Suci; Kusumaningsih, Widya; Violinda, Qristin (Jayapangus Press, 2025)
Education plays a strategic role in improving the quality of human resources, which is highly dependent on teacher competence, especially pedagogical competence. However, research shows that teacher pedagogical competence still needs to be improved. Academic supervision by the principal is the main strategy in improving this competence. This study aims to describe and analyze the implementation of academic supervision at SMA Negeri 1 Gubug with a descriptive qualitative approach. Data were collected through interviews, observation, and documentation, then analyzed through presentation, reduction, and drawing conclusions. The results of the study showed that 1) academic supervision planning was carried out periodically at the beginning of the school year and reviewed every semester. The supervision team consisting of the principal, vice principal, and senior teachers, prepared a supervision program based on the results of previous supervision and analysis of educational report cards, making schedules, preparing instruments, and selecting appropriate supervision approaches and techniques, 2) the implementation of academic supervision was carried out according to schedule without disrupting learning covering three stages: pre-observation, observation, and post-observation. Pre-observation was carried out by checking the learning administration and discussing teacher self-development in a relaxed atmosphere. Observation was carried out by observing the learning process directly in the classroom. Post-observation focuses on evaluating learning that has been carried out by teachers, 3) evaluation and follow-up of academic supervision involves joint reflection between supervisors and teachers to provide constructive feedback. individually through direct input and motivation to teachers, and classically through training facilitation such as In House Training (IHT), Workshops, and participation in Learning Communities (Kombel) and Subject Teacher Deliberations (MGMP). With structured academic supervision, improving teachers' pedagogical competence can be done optimally and sustainably.